Puerperal women’s satisfaction with their delivery - Tavares, Beatriz Barco; Leite Belisário, Cintia Rodrigues; Cicuto, Ariane Garcia (Investigación y Educación en Enfermería, 2012)
<!-- [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--> Objective. To assess puerperal women’s level of satisfaction with their delivery. Methodology. A descriptive study was developed at a teaching hospital in São José do Rio Preto (Brazil between July and December 2010. Participants were 200 puerperal women from the neonatal screening service, who completed the Delivery Experience and Satisfaction Questionnaire to measure their satisfaction level. Answer options for each question range between 1 and 10 (maximum satisfaction). Results. The puerperal women’s mean age was 28 years; 96% had a partner; all women had participated in prenatal care; 82% were submitted to caesarean section. Satisfaction with pain management during labor ranged from 8.5 for caesarean section to 6 for normal birth. In comparison with the vaginal birth group, women subject to c-section showed greater satisfaction with postpartum pain intensity (8.7 versus 6.2) and less satisfaction with labor (6.0 versus 8.5) and delivery (7.1 versus 9.0). Conclusion. Without any difference per delivery type, women’s satisfaction level with their delivery was high. Women who underwent caesarean section obtained higher satisfaction scores for postpartum pain management, while women who underwent vaginal birth manifested greater satisfaction with pain control during labor and delivery.